Legal Issues for Ensuring Phytosanitary Safety and Environmental Protection - ORYNTAEV, Zhambyl; AKSHATAYEVA, Zhanna; AIGARINOVA, Gulnar; KALKANOVA, Zhanna; RASHEVA, Gulnur (Journal of Environmental Management and Tourism, 2020)
Phytosanitary safety is determined by the possibilities of ensuring food safety, which guarantees the sustainable development of the state and improvement of the quality of life. The specifics of ensuring regulation of phytosanitary safety are the principles of equilibrium regulation and the establishment of a holistic perception of safety parameters on the part of both regulatory bodies and regulatory agencies. The novelty of the study is determined by the fact that the formation of safety in the field of phytosanitary surveillance is determined not only by directly controlling the quality of plant raw materials, but also by the food products and materials that are subsequently produced from them. The authors have demonstrated aspects of the implementation of integrated surveillance, analysed the legal systems of various countries that can be sources of supervision and control in the field of phytosanitary safety. The article shows the possibility of expanding the standardisation programs of food raw materials and finished products for phytosanitary facilities. The practical significance of the study is determined by the fact that ensuring phytosanitary safety on a global scale will reduce the need for food supply of individual countries and increase the depth of processing of current food technologies. Ultimately, this will affect the possibility of intensifying social development programs of individual countries and regions.